Perspectives on birth among families and health care professionals in the Arctic: A scoping review protocol ... - Jensen, Tenna; Olesen, Ingelise; Rubin, Sofie Emma (OSF Registries, 2022)
The objective of this scoping review is to scope and map existing research, providing perspectives on birth from the views of families and health care professionals in remote communities in the Arctic. The overall main research question of the review is defined as: ‘What are the perspectives on birth in remote communities in the Arctic? Furthermore, two sub questions has been developed: 1) ‘How does families and health care professionals perceive birth in remote communities in the Arctic?’ and 2) 'What are the barriers and facilitators to local birth giving in remote communities in the Arctic?’ ...